Kegunaan Sub-Martingale dalam Masalah Storan - Shahran, Mohd Kidin (1992)
Consider a water tank with a finite capacity. With the help of the Sub-Martingale theory a lower bound of the expectation of the minimum time the tank takes to become empty is found.